2013
DOI: 10.4103/0189-6725.125403
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of varicocele in the adolescent: Our experience from Benin

Abstract: TH due to varicocele is better studied by ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Most studies have reported varicoceles to be more common on the left in both sub-fertile men and normal population [12][13][14][15]. Our findings were consistent with these.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Most studies have reported varicoceles to be more common on the left in both sub-fertile men and normal population [12][13][14][15]. Our findings were consistent with these.…”
Section: Discussionsupporting
confidence: 95%
“…Is there a relationship with race or geographical location? Fiogbe et al in Cotonou [15], also in West Africa, in a random screening of 2724 adolescents using scrotal US reported a bilateral prevalence of 87.6%. However, Gat et al [13] using a combination of multiple diagnostic tools, including scrotal US and venography also found a bilateral prevalence of 80.7% in infertile men and suggested that varicocele may actually be a bilateral disease.…”
Section: Discussionmentioning
confidence: 94%
“…A venous reflux of the pampiniform plexus within the spermatic cord of longer than 2 s detected with CDU in orthostatism and with a Valsalva maneuver constituted a varicocoele (i.e., significant reflux) (Sheehan et al ., ). The reflux was assessed semiquantitatively in orthostatism according to the literature (Fiogbe et al ., ) which indicates three grades of reflux: (i) significant reflux present only during the Valsalva maneuver (discontinuous reflux); (ii) significant reflux present even in the absence of Valsalva maneuver but increased by the Valsalva maneuver (continuous reflux increased by Valsalva), and (iii) significant reflux present even in the absence of the Valsalva maneuver but not increased by the Valsalva maneuver (continuous reflux not modified by the Valsalva maneuver). The CDU scrotal examinations were carried out according to the American College of Radiology guidelines (American College of Radiology et al .…”
Section: Methodsmentioning
confidence: 99%
“…Using US, Fiogbe et al [36] assessed the presence of subclinical varicocele in 81 adolescents aged 10-19 years who had a varicocele on one side. In 50 patients (61.7%), subclinical varicocele was detected.…”
Section: Subclinical Varicocele In Adolescentsmentioning
confidence: 99%